2020
DOI: 10.1021/acs.estlett.0c00709
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Failure Modes of NSF/ANSI 53 Lead-Certified Point-of-Use Pitcher and Faucet Filters

Abstract: NSF/ANSI 53 lead-certified point-of-use filters (POUs) have been distributed to consumers in many cities facing lead-in-water crises including Washington, D.C., Flint, MI, Newark, NJ, and University Park, IL. After questions repeatedly arose about POU effectiveness in treating samples with relatively high levels of lead, we examined 10 POU pitcher and faucet filter brands under extreme conditions (e.g., ≤200% of rated capacity, influent lead levels of ≈1000 μg/L). Our tests sought to validate the successful pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…The NSF/ANSI 53 certified POU filters may face underperformance under certain conditions. ,− Recently, a field investigation in Newark found that Pb phosphate nanoparticles (diameter: <0.1 μm) can penetrate properly installed and functional POU filters with total Pb concentrations in the filtered water as high as 45 μg/L . Moreover, the NSF/ANSI 53 certification protocol challenges filters by using a Pb­(NO 3 ) 2 solution to develop Pb carbonates and oxides that are 0.1–1.2 μm in size .…”
Section: Introductionmentioning
confidence: 99%
“…The NSF/ANSI 53 certified POU filters may face underperformance under certain conditions. ,− Recently, a field investigation in Newark found that Pb phosphate nanoparticles (diameter: <0.1 μm) can penetrate properly installed and functional POU filters with total Pb concentrations in the filtered water as high as 45 μg/L . Moreover, the NSF/ANSI 53 certification protocol challenges filters by using a Pb­(NO 3 ) 2 solution to develop Pb carbonates and oxides that are 0.1–1.2 μm in size .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that point-of-use filters may be poorly suited to removing highly dispersed colloidal lead. , Given the dispersive properties of sodium silicates, a potential risk of silicate treatment is the dispersion of lead-rich colloids. This effect is analogous to the negative side effects of polyphosphate (another common class of sequestrants) , and sometimes even orthophosphate. ,,, The higher total lead concentrations due to silicate that have been reported in some previous studies ,, maybe due in part to dispersion (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…NSF/ANSI 53 certified POU filters have been distributed in cities facing lead-in-water crises, such as Washington, DC. Flint, MI, Newark, NJ, University Park, IL, and Benton Harbor, MI. , However, field sampling and lab tests have found conditions at which POU filters did not work well. , In particular high concentrations of particulate lead (1–45 μg Pb/L) were observed in the effluent of POU filters in Newark, NJ . When challenged in the laboratory with water containing lead phosphate particles (150 μg Pb/L, pH 7, and 2 mM ionic strength), these filters only removed 55% at low hardness .…”
Section: Challengesmentioning
confidence: 99%